Accelerating Concept Learning via Sampling - Baci, Alkid; Heindorf, Stefan (CIKM)

Calibration of Large Coherent MIMO Radar Arrays: Channel Imbalances and 3D Antenna Positions - Greiff, Christian; Mateos-Núñez, David; Simoni, Renato; González-Huici, Maria; Kruse, Stephan; Scheytt, J. Christoph; Kolk, Karl; Höller, Christian; Kurz, Heiko Gustav; Meinecke, Marc-Michael; Gisder, Thomas (2023 24th International Radar Symposium (IRS))
One of the main challenges for next generation automotive radars is the improvement of angular resolution to a sub-degree level. In this context, wide aperture automotive radars of 1m length or more and resolution close to 0.1° in azimuth and 0.5° in elevation could be beneficial. To enable coherent processing of arrays with such large aperture, prior (i.e offline) and online calibration are necessary: channel imbalances (gains and phases) and three dimensional coordinates of transmit and receive elements need to be determined. We propose a calibration strategy based on alternating steps between the two subtasks of i) channel imbalance estimation with ‘known’ array positions, by applying a singular value decomposition to the resulting tensor calculus problem; and ii) antenna position estimation with ’known’ channel imbalances, by numerically maximizing the Bayesian posterior probability; in both cases operating on range/Doppler snapshots of disjoint targets (with potentially unknown locations). Simulation studies based on the parameters of a MIMO 8x6 linear sparse array show promising results as long as the initial position errors do not exceed half a wavelength (2mm), beyond which we observe strong effects of ambiguity. Experimental results with real measurements show that after calibration in laboratory conditions, our MIMO 8x6 demonstrator with 50cm aperture is able to resolve two targets at the same range with angular separation at least as close as 0.4°.

Lehrentwicklung durch Scholarship of Teaching and Learning – mit SoTL Hochschullehre beforschen, weiterentwickeln und teilen - Vöing, Nerea; Arnold, Maik; Reisas, Sabine

Scholarship of Teaching and Learning (SoTL) als Motor für eine inter- und transdisziplinäre Hochschuldidaktik - Arnold, Maik; Vöing, Nerea; Reisas, Sabine (Hochschulbildung: Lehre und Forschung)
SoTL ist eine forschungsbasierte Haltung, die die Hochschullehre verbessern und innovieren will. Das deutschsprachige SoTL-Netzwerk hat fünf Thesen formuliert, die SoTL als Grundhaltung und Motor für Lehrentwicklung betonen. Der Beitrag diskutiert diese Thesen und stellt Aktivitäten des Netzwerks vor, die SoTL an Hochschulen und Universitäten fördern und vernetzen wollen. Dabei wird auch die Rolle der »Teacher-Researcher« hervorgehoben.

Multi-Objective Optimization for Sparse Deep Neural Network Training - Hotegni, Sedjro Salomon; Peitz, Sebastian; Berkemeier, Manuel Bastian (arXiv:2308.12243)
Different conflicting optimization criteria arise naturally in various Deep Learning scenarios. These can address different main tasks (i.e., in the setting of Multi-Task Learning), but also main and secondary tasks such as loss minimization versus sparsity. The usual approach is a simple weighting of the criteria, which formally only works in the convex setting. In this paper, we present a Multi-Objective Optimization algorithm using a modified Weighted Chebyshev scalarization for training Deep Neural Networks (DNNs) with respect to several tasks. By employing this scalarization technique, the algorithm can identify all optimal solutions of the original problem while reducing its complexity to a sequence of single-objective problems. The simplified problems are then solved using an Augmented Lagrangian method, enabling the use of popular optimization techniques such as Adam and Stochastic Gradient Descent, while efficaciously handling constraints. Our work aims to address the (economical and also ecological) sustainability issue of DNN models, with a particular focus on Deep Multi-Task models, which are typically designed with a very large number of weights to perform equally well on multiple tasks. Through experiments conducted on two Machine Learning datasets, we demonstrate the possibility of adaptively sparsifying the model during training without significantly impacting its performance, if we are willing to apply task-specific adaptations to the network weights. Code is available at https://github.com/salomonhotegni/MDMTN.

Efficient time stepping for numerical integration using reinforcement learning - Dellnitz, Michael; Hüllermeier, Eyke; Lücke, Marvin; Ober-Blöbaum, Sina; Offen, Christian; Peitz, Sebastian; Pfannschmidt, Karlson (SIAM Journal on Scientific Computing)
Many problems in science and engineering require an efficient numerical approximation of integrals or solutions to differential equations. For systems with rapidly changing dynamics, an equidistant discretization is often inadvisable as it results in prohibitively large errors or computational effort. To this end, adaptive schemes, such as solvers based on Runge–Kutta pairs, have been developed which adapt the step size based on local error estimations at each step. While the classical schemes apply very generally and are highly efficient on regular systems, they can behave suboptimally when an inefficient step rejection mechanism is triggered by structurally complex systems such as chaotic systems. To overcome these issues, we propose a method to tailor numerical schemes to the problem class at hand. This is achieved by combining simple, classical quadrature rules or ODE solvers with data-driven time-stepping controllers. Compared with learning solution operators to ODEs directly, it generalizes better to unseen initial data as our approach employs classical numerical schemes as base methods. At the same time it can make use of identified structures of a problem class and, therefore, outperforms state-of-the-art adaptive schemes. Several examples demonstrate superior efficiency. Source code is available at https://github.com/lueckem/quadrature-ML.

Scholarship of Teaching and Learning (SoTL) als Motor für eine inter- und transdisziplinäre Hochschuldidaktik - Arnold, Maik; Vöing, Nerea; Reisas, Sabine (Hochschulbildung: Lehre und Forschung)
SoTL ist eine forschungsbasierte Haltung, die die Hochschullehre verbessern und innovieren will. Das deutschsprachige SoTL-Netzwerk hat fünf Thesen formuliert, die SoTL als Grundhaltung und Motor für Lehrentwicklung betonen. Der Beitrag diskutiert diese Thesen und stellt Aktivitäten des Netzwerks vor, die SoTL an Hochschulen und Universitäten fördern und vernetzen wollen. Dabei wird auch die Rolle der »Teacher-Researcher« hervorgehoben.

Modeling and Parameterization for a 3D Simulation of Clinching with an Extensible Die - Rossel, M.; Meschut, G. (Lecture Notes in Mechanical Engineering)

Training matters: Heading incidence and characteristics in children's and youth football (soccer) players - Reeschke, Rebecca; Haase, Franziska Katharina; Dautzenberg, Lena; Krutsch, Werner; Reinsberger, Claus (Scandinavian Journal of Medicine & Science in Sports)
Abstract Objective Concerns about short‐ and long‐term consequences of repetitive heading contributed to heading restrictions in youth football in some countries. This prospective longitudinal cohort study aims to describe heading exposure in children's and youth football over two seasons using standardized video analysis. Methods All matches and training sessions of a male Under‐11 ( n = 29), Under‐15 ( n = 28), Under‐19 ( n = 38), and female Under‐17 ( n = 39) team were videotaped during the seasons 2019–2020 and 2020–2021. Heading frequencies and characteristics were analyzed. Individual heading exposure is presented as average incidence rates (IR) per 1000 match/training hours. Results In 275 matches and 673 training sessions, 22 921 headers were observed. Heading IR per player in matches was 1256 (Under‐11 m), 1608 (Under‐15 m), 1050 (Under‐17 f), and 1966 (Under‐19 m). In training sessions, IR per player was 739 (Under‐11 m), 2206 (Under‐15 m), 1661 (Under‐17 f), and 1419 (Under‐19 m). Five Under‐15 males headed the ball five to eight times per training on average. Most headers were performed without heading duels. Flight distance was predominantly 5–20 m (54%) in matches and <5 m (65%) in training. While head impact location most frequently was at frontal areas, one‐third of all headers in Under‐11 in matches hit temporal, parietal, and occipital parts of the head. Conclusion Heading incidence was low in the youngest age group, whereas (predominantly five) Under‐15 males showed very high heading exposures in training. In assessment and regulation of heading burden, training sessions and individual heading behavior should specifically be addressed. Recommendations for heading the ball in practice should account for individual and age‐related differences.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

GaMoVR: Gamification-Based UML Learning Environment in Virtual Reality - Yigitbas, Enes; Schmidt, Maximilian; Bucchiarone, Antonio; Gottschalk, Sebastian; Engels, Gregor (Science of Computer Programming)

Comparison of Required Competences and Task Material in Modeling Education - Soyka, Chantal; Ullrich, Meike; Striewe, Michael; Schaper, Niclas (Enterprise Modelling and Information Systems Architectures)
The reform of the European academic landscape with the introduction of bachelor's and master's degree programs has brought about several profound changes for teaching and assessment in higher education. With regard to the examination system, the shift towards output-oriented teaching is still one of the most significant challenges. Assessments have to be integrated into the teaching and learning arrangements and consistently aligned towards the intended learning outcomes. In particular, assessments should provide valid evidence that learners have acquired competences that are relevant for a specific domain. However, it seems that this didactic goal has not yet been fully achieved in modeling education in computer science. The aim of this study is to investigate whether typical task material used in exercises and exams in modeling education at selected German universities covers relevant competences required for graphical modeling. For this purpose, typical tasks in the field of modeling are first identified by means of a content-analytical procedure. Subsequently, it is determined which competence facets relevant for graphical modeling are addressed by the task types. By contrasting a competence model for modeling with the competences addressed by the tasks, a gap was identified between the required competences and the task material analyzed. In particular, the gap analysis shows the neglect of transversal competence facets as well as those related to the analysis and evaluation of models. The result of this paper is a classification of task types for modeling education and a specification of the competence facets addressed by these tasks. Recommendations for developing and assessing student's competences comprehensively are given.
Keywords: conceptual modeling; higher education; competence-oriented assessment; task analysis; graphical modeling

Methodical Approach to Reducing Design Time by using Neural Networks in Early Stages of Concept Development - Ott, Manuel; Meihöfener, Niclas; Mozgova, Iryna (Proceedings of the 34rd Annual International Solid Freeform Fabrication Symposium 2023)
Modern companies often face various challenges in concept development of products or systems. Design engineers prepare initial concepts as 3D models. These are then simulated by computational engineers. If requirements are not met, this necessitates an iterative process that runs between the design and computation departments until a valid concept is created. Design methods such as topology optimization are often used here. The upcoming result is then attempted to be adapted to certain manufacturing processes. These iteration loops can sometimes take a very long time, since the model construction and structural optimization generate large computational efforts. The present work shows on an example a methodical approach, which represents a first proof of concept, to solving this problem, including a description of methods and techniques, as well as possible problems in a detailed analysis concerning training data for neural networks and their abstraction capabilities. It is evident that additional research work needs to be conducted for further utilization in order to address all arising questions.

Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice - A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience

Learning and Memory in Sports - Weigelt, Matthias; Krause, Daniel; Güldenpenning, Iris (Sport and Exercise Psychology)

Lessons learned from a global review study of physics textbook evaluation and its implications for teaching and learning in the classroom - Jonas-Ahrend, Gabriela; Fraser-Abder, Pamela; Kapanadze, Marika; Joubran, Fadeel; Mazzolini, Alexander

A Sub-Threshold Microwave RFID Tag Chip, Compatible With RFID MIMO Reader Technology - Haddadian, Sanaz; Scheytt, J. Christoph; von Bögel, Gerd; Grenter, Thorben (IEEE Journal of Radio Frequency Identification)
We present a fully integrated radio frequency identifications transponder chip operating at 5.8 GHz, which is compatible with the class-1 generation-2 of the Electronic Product Code protocol (EPC-C1 G2). The tag chip including the analog front-end and the digital baseband processor, are designed in the sub-threshold regime (0.5 V) with a total supply current of less than 50 μA. As a power scavenging unit, a single-stage differential-drive rectifier structure is designed and fabricated with standard threshold voltage (SVT) MOS elements in a commercial 65-nm CMOS process, to provide 0.8 V of rectified voltage. Measurements performed on the fabricated single-stage structure show a maximum power conversion efficiency of 69.6% for a 22 kΩ load and a sensitivity of -12.5 dBm, which corresponds to more than 1 m of reading range. The power conversion efficiency at this range is about 64%.

Design of individual simulation games in manufacturing companies for game-based learning - Machon, Fabian; Gabriel, Stefan; Latos, Benedikt; Holtkötter, Christoph; Lütkehoff, Ben; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Impact of 3D Curvature on the Polarization Orientation in Non-Ising Domain Walls - Acevedo-Salas, Ulises; Croes, Boris; Zhang, Yide; Cregut, Olivier; Dorkenoo, Kokou Dodzi; Kirbus, Benjamin; Singh, Ekta; Beccard, Henrik; Rüsing, Michael; Eng, Lukas M.; Hertel, Riccardo; Eliseev, Eugene A.; et al. (Nano Letters)
Ferroelectric domain boundaries are quasi-two-dimensional functional interfaces with high prospects for nanoelectronic applications. Despite their reduced dimensionality, they can exhibit complex non-Ising polarization configurations and unexpected physical properties. Here, the impact of the three-dimensional (3D) curvature on the polarization profile of nominally uncharged 180° domain walls in LiNbO3 is studied using second-harmonic generation microscopy and 3D polarimetry analysis. Correlations between the domain-wall curvature and the variation of its internal polarization unfold in the form of modulations of the Néel-like character, which we attribute to the flexoelectric effect. While the Néel-like character originates mainly from the tilting of the domain wall, the internal polarization adjusts its orientation due to the synergetic upshot of dipolar and monopolar bound charges and their variation with the 3D curvature. Our results show that curved interfaces in solid crystals may offer a rich playground for tailoring nanoscale polar states.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Pseudo-Labeling Machine Learning Algorithm for Predictive Maintenance of Relays - Winkel, Fabian; Wallscheid, Oliver; Scholz, Peter; Böcker, Joachim (IEEE Open Journal of the Industrial Electronics Society)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

Run-to-Failure Relay Dataset for Predictive Maintenance Research With Machine Learning - Winkel, Fabian; Deuse-Kleinsteuber, Johannes; Böcker, Joachim (IEEE Transactions on Reliability)
Keywords: Electrical and Electronic Engineering; Safety; Risk; Reliability and Quality